Two old broads : stuff you need to know that you didn't know you needed to know - Hecht, M. E.; Goldberg, Whoopi, 1955- (Harper Horizon, 2022)
Both hilarious and helpful, this practical and unapologetic health and lifestyle guide tells it like it is for women who left middle age in the dust and want to be present, positive, and as extraordinary as ever in their golden years.